Venous Thrombosis in Suspected Pulmonary Embolism: Incidence Detectable by Doppler Ultrasound - Barnes, Robert W.; Kinkead, Lewis R.; Wu, Kenneth K.; Hoak, John C. (Thrombosis and Haemostasis, 1976)
Doppler ultrasound has been used to screen patients for venous thrombosis with an accuracy of 94% compared to venography. Of 168 patients with suspected pulmonary embolism, only 48 (28%) had a source of venous thrombosis detectable by Doppler examination. The calf and iliofemoral venous segments were the two most common sites of involvement. When compared to Doppler examination, clinical assessment of the legs was falsely negative in 15% and falsely positive in 54% of patients. The highest incidence of venous thrombosis detected by Doppler examination (49%) was in the group of patients with a positive lung scan and a normal chest film. Doppler evidence of venous thrombosis was present in only 21% of patients with both a positive scan and an abnormal chest film. One-third of the patients with suspected pulmonary embolism had a negative lung scan. The most common conditions mimicking pulmonary embolism were congestive heart failure, pneumonia, chronic lung disease and atelectasis. Patients with suspected pulmonary emboli frequently have no demonstrable source of thrombosis and may deserve more thorough angiographic evaluation for proper diagnosis and therapy.